SOCIAL MEDIA UTILISATION AMONG UNDERGRADUATES IN UNIVERSITY OF ILORIN, ILORIN, NIGERIA - YAHYA, Saheed Olalekan; IBRAHIM, Taye; KAREEM, Ibrahim Ahmed (Ilorin Journal of Education, 2023)
The study was a survey type using purposive and proportional sampling techniques to draw a sample of 300 undergraduates in 300 and 400 levels of the University of Ilorin, Ilorin, Nigeria respectively. The main research instrument employed for data collection was researchers’ designed questionnaire entitled utilization of social media among undergraduates in University of Ilorin, Ilorin, Nigeria. The reliability of the instrument was determined by administering twenty copies of the questionnaire to randomly selected undergraduates of Al-Himah University, Ilorin. Cronbach alpha reliability was used to check for the instrument’s internal consistency which yielded 0.79 showing that the instrument was reliable. Four research questions were answered using frequency counts and percentages for research questions one to three and research question four answered using mean and rank order. Two hypotheses were generated and analysed with t[1]test for hypothesis one and ANOVA for hypothesis two. The findings of the study indicated that over 50% of the respondents subscribed to and used most of the social media listed, 129 (45%) of the respondents used social media for educational purposes, 98 (32.7%) of the respondents used social media for entertainment and73 (24.3%) of the respondents used social media for socialization. It was recommended among others that: undergraduates should give priority to academic utilization of social media than to entertainment and socialization. Undergraduates from other discipline should emulate the medical, sciences, engineering and law undergraduates’ habit of using social media for educational purposes than for entertainment and socialization.